Teachers' experiences of ICT training in Nepal: how teachers in rural primary schools learn and make progress in their ability to use ICT in classrooms. Issue 3 (27th May 2022) - Rana, Karna; Greenwood, Janinka; Henderson, Robyn
ABSTRACT: This article reports on teachers' experiences of ICT training in rural areas of Nepal. It discusses aspects of policy documents to help understand the Nepali educational context, before highlighting the challenges of establishing and maintaining infrastructure and professional learning opportunities across a country with challenging terrain and extreme environmental conditions. It then examines teachers' perceptions in five rural primary schools about their experiences of training to use modern educational technologies in instructional activities. The findings indicate that none of the teachers received training in the use of ICT in their initial teacher education and that the Government has allowed non-governmental organisations to provide ICT infrastructure and training for rural schools and teachers. Although this is a small study, it offers insights into the gap between policy and practice and highlights the contextual challenges of Nepal's attempts to operate on a global educational level as well as the challenges for teachers.